Research-based findings on scope of liposome-based cosmeceuticals: an updated review - Tapan Kumar Shaw; Paramita Paul; Bappaditya Chatterjee (Future Journal of Pharmaceutical Sciences, 2022)
Abstract Background Cosmeceuticals are cosmetic products with biologically active components that have drug-like benefits. Cosmeceuticals are currently rapidly growing segments encompassing the personal care industry and numerous topical cosmetics-based therapies for treating different skin conditions. The barrier nature of skin causes limitations to topical treatment. The effectiveness of this cosmeceutical product has been enhanced a few folds by using nanotechnological modifications. Main body PubMed electronic searches for the literature were performed using combinations of the following terms: “cosmeceutical,” “liposome-based cosmeceuticals,” “acne and liposome,” “photo-aging and liposome,” “hyperpigmentation and liposome,” “wrinkles and liposome,” “fungal infections and liposome,” and “hair damage and liposome” from the earliest publication date available to January 5, 2022. Among the various nanotechnological approaches, liposomes offer numerous advantages such as topical cosmeceutical products, starting from improved moisturization, biodegradability, biocompatibility, enhanced permeation and retention, improved bioavailability of the active ingredients, increased esthetic appeal of cosmeceutical products, slow and extended dermal release. This review outlines various liposome-based cosmeceutical products that has been investigated to treat skin disorders such as photoaging, wrinkles, hyperpigmentation, hair damage and fungal infections. Conclusion Liposome-based cosmeceuticals provide a better opportunity to deliver therapeutic moiety for various skin conditions and offer potential promise for future clinical applications. Graphical Abstract